Alternative Cropping Systems with Limited Irrigation - A. Schlegel (Kansas Agricultural Experiment Station Research Reports, 2016)
A limited irrigation study involving six cropping systems was initiated at the Southwest Research-Extension Center near Tribune, KS, in 2012. The cropping systems were two annual systems (continuous corn [C-C] and continuous grain sorghum [GS-GS]) and four 2-year systems (corn-sorghum [C-GS]), corn-sunflower [C-SF], corn-winter wheat [C-W], and corn-wheat/double sunflower [C-W/SF]). In 2015, corn yields were lower following corn than other crops while wheat and grain sorghum yields were similar for all rotations. This tended to agree with the 3-year average yields except for average sorghum yields being higher following corn than sorghum. Sunflowers were destroyed by rodents and no yields were obtained.
Keywords: alternative cropping systems; limited irrigation; corn; grain sorghum; sunflower; winter wheat; irrigation management